The Effect of Blue Light Exposure on Sleep Quality and Student Productivity in the Digital Learning Era - Diana Chandra Dewi; Yuli Hardina (CV. Get Press Indonesia, 2026)
The proliferation of digital learning platforms has substantially increased student screen time, raising concerns about blue light (415–455 nm) exposure and its effects on sleep quality and cognitive productivity. This cross-sectional study examined 216 undergraduate students from three Javanese public universities (2023–2024). Blue light exposure was quantified using lux-meter spectrophotometry; sleep quality via the Pittsburgh Sleep Quality Index (PSQI); and productivity through Grade Point Average (GPA), Perceived Productivity Scale (PPS), and cognitive tests (Trail Making Test A/B, digit span). Regression and mediation analyses were performed. Students with ≥3 hours nightly pre-sleep blue light exposure had significantly poorer PSQI scores (8.6±1.8 vs. 4.1±1.2; p<0.001) and 18.3% lower academic productivity scores. Sleep quality partially mediated the blue light–productivity relationship (β=-0.41, 95% CI: -0.54 to -0.28). Use of blue light-filtering glasses and Night Mode significantly attenuated these effects (p=0.012). These findings provide empirical evidence for evidence-based digital wellness policies in Indonesian higher education.